Theories of the pathogenesis of schizophrenia - Justyna Dąbrowska; Magdalena Wójcik; Julita Szarpak; Damian Bator; Joanna Milanowska; Hubert Nieścior (Kazimierz Wielki University, 2020)
Introduction: Schizophrenia is one of the most serious and frightening of all mental illnesses. It affects almost 1% of the population worldwide. The main concept and treatment of schizophrenia are based on the dopaminergic hypothesis. However, accumulating evidence has shown that the core pathophysiology of schizophrenia might involve dysfunction in dopaminergic, glutamatergic, serotonergic, and gamma-aminobutyric acid signaling. The aim of the study: The purpose of this systemic review was to collect and analyse current and new information on the pathogenesis of schizophrenia. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: schizophrenia, dopamine hypothesis, serotoninergic hypothesis, hypothesis of schizophrenia . Description of the state of knowledge: There are evidence that pathogenesis of schizophrenia include dysfunction in dopaminergic, serotoninergic, GABAergic, glutamatergic systems. The use of drugs that act on any of these systems reduces the symptoms of the disease. Nicotinic receptors may also be the target for drugs in treatment of schizophrenia. Studies about the role of nicotinic receptors in pathogenesis of schizophrenia show that it normalize many of the sensory processing deficits found in schizophrenia. Summary: Despite the fact that current concept and treatment are still based on the dopaminergic hypothesis of the disease, existing theories and each new theory, open up different ways for treating schizophrenia. Considering that schizophrenia is one of the most serious and frightening of all mental illnesses and has major public health implications, more research about pathogenesis and ways of treatment is needed.